AKTIVITAS ANTIBAKTERI SEDUHAN BIJI PEPAYA (CARICA PAPAYA L) TERHADAP ESCHERICHIA COLI, SALMONELLA THYPI DAN STAPHLYCOCUS AUREUS - Anggun Rahmi Ayu Lestari; Sari Anggraini Syahfitri; Sofi Tri Cahyo; Isna Wardaniati; Muhammad Azhari Herli (JURNAL FARMASI DAN MAKANAN, 2018)
Papaya (Carica papaya L) is a very popular and important fruit in the tropical part where as a nutritious plant that can cure diseases. every part of papaya plants can be utilized start, roots, stems, leaves, fruit and even seeds of fruit. Traditionally papaya seeds can be used as a roundworm drug indigestion, diarrhea, skin diseases, colds, and as a source to get oil with fatty acid content. This research uses extract and steep seeds on papaya fruit with Escherichia coli test bacteria, Salmonella typhi, and Staphlycoccus aureus. From this research we get the result of inhibitory power : Escherichia coli at concentrations of 20%, 40%, 60% 80% and 100% were 8.72 mm; 9.53 mm; 10.61 mm; 10.99 mm; and 12.19 mm. Salmonella thypi at concentrations of 20%, 40%, 60% 80% and 100% were 7.07 mm; 8.63 mm; 9.54 mm; 9.78 mm; and 10.16 mm. Staphylococcus aureus at concentrations of 20%, 40%, 60% 80% and 100% was 6.4 mm; 6.8 mm; 7.8 mm; 7.9 mm; and 10.1 mm.